1995
DOI: 10.1111/j.1540-4781.1995.tb05447.x
|View full text |Cite
|
Sign up to set email alerts
|

Error Gravity in Learners' Spoken Russian: A Preliminary Study

Abstract: The present study was designed to begin the work to establish a hierarchy of error gravity for different types of common errors in American learners' spoken Russian. Respondents included native speakers of Russian and English, teachers and non‐teachers, and residents of Russia and the U. S. Respondents were asked to compare a series of paired sentences that were identical except for a particular error and to select which sentence they found to be less irritating. The sentences were selected from oral proficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Rifkin's (1995) polling for perception of errors among speakers of Russian found learners’ mistakes in aspect to be in the middle of the spectrum of error gravity. In the subpopulation of Russians living in Russia who were not teachers of Russian (the likely target audience for learners at the Advanced level), errors in aspect ranked 3 on an eight‐point scale (1 to 9) of acceptability.…”
Section: Perceptions Of Aspectual Errorsmentioning
confidence: 99%
“…Rifkin's (1995) polling for perception of errors among speakers of Russian found learners’ mistakes in aspect to be in the middle of the spectrum of error gravity. In the subpopulation of Russians living in Russia who were not teachers of Russian (the likely target audience for learners at the Advanced level), errors in aspect ranked 3 on an eight‐point scale (1 to 9) of acceptability.…”
Section: Perceptions Of Aspectual Errorsmentioning
confidence: 99%
“…There have been a number of studies of the acquisition of Russian as a second language (Gor et al, 2009;Hasko, 2009;Rifkin, 1995;Rosengrant, 1987;Thompson, 1997) as well as a heritage language (Andrews, 2001;Isurin & Ivanova-Sullivan, 2008;Kagan, 2001;Kagan & Dillon, 2001;Polinsky, 2000;Polinsky, 2008;Polinsky & Kagan, 2007;Romanova, 2008). These studies showed that heritage and second language learners of Russian, having very different backgrounds, often make errors in the same categories (word order, tense and aspect, case errors).…”
Section: My Studymentioning
confidence: 99%
“…For instance, the grammatical system of the Russian language is generally very difficult to master for native speakers of English because of its extensive morphology, and verbs of motion are reported to be one of the main challenges (Hasko, 2009;Gor et al, 2009). Besides errors in production of verbs of motion, learners of Russian usually make errors in case and gender, in voice, conjugation, aspect and tense (Rifkin, 1995).…”
Section: Second Language Learners Of Russianmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some foreign-accented versions of other languages have also come under scrutiny (e.g. Swedish (Abelin andBoyd 2000, Boyd 2003), German (Missaglia 1999, Gut 2007, Spanish (Schairer 1992), French (Mareuil, Brahimi and Gendrot 2011) and Russian (Rifkin 1995)), although such studies are still relatively infrequent in comparison with the former. This means, in consequence, that while we know much about reactions to non-native English, attitudes towards foreign accents in other languages, such as Polish, still remain to be examined in detail.…”
Section: Introductionmentioning
confidence: 99%